A crucial factor towards a sustainable process for municipal wastewater treatment: Fouling effects of different statuses of biomass in the membrane bioreactors with no sludge discharge. (10th August 2018) - Zheng, Yi; Tang, Bing; Ye, Jianwen; Bin, Liying; Li, Ping; Xue, Feifei; Huang, Shaosong; Fu, Fenglian; Xiao, Yiliang
Abstract: This work aimed at illustrating a crucial factor towards a sustainable municipal wastewater treatment process, namely, the membrane fouling caused by different statuses of biomass in the membrane bioreactors (MBRs) with no sludge discharge, and tried to explore the essential reasons leading to membrane fouling. By parallelly operating the MBRs with or without bio-carriers for 90 days under the same conditions, their operating characteristics and the accumulated membrane foulants were comparatively studied by using multi-methods. The results indicated that the added bio-carriers mitigated the membrane fouling, especially inhibited the formation of the reversible and the permanent resistance of membrane modules, and reduced the accumulation of foulants on membrane surface. When the trans-membrane pressure value of the bioreactor with bio-carriers reached 32.5 kPa for the first time, the trans-membrane pressure value of the bioreactor without bio-carriers had reached 32.5 kPa for the third time. The growing status of biomass was changed by the bio-carriers, which influenced the micro-habitat of microorganisms and varied the structure of microbial communities within the MBRs. The variation of the growing status of biomass is an essential reason leading to exhibiting differences in the membrane fouling of these MBRs. Graphical abstract: Image 1 Highlights: Two MBRs with no sludge discharge were stably operated for 90 days. The growing status of biomass in MBRs heavily influenced membrane fouling. Bio-carriers changed the micro habitat of MBRs and the tendency of membrane fouling. SMP and EPS played an important role in causing permanent membrane fouling.